2014
DOI: 10.4184/asj.2014.8.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome in Patients with Early versus Delayed Decompression in Cervical Spine Trauma

Abstract: Study DesignProspective observational study.PurposeTo assess the clinical outcome after early versus late decompression for traumatic cervical cord injury.Overview of LiteratureTraumatic spinal cord injury is common globally with the most tragic outcomes in the cervical spine. Although recent studies have shown that early decompression results in more favourable outcome, its authority is yet to be established.MethodsStudy on 98 patients with a traumatic cervical cord injury was conducted over a period of 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…A cutoff value approximating 19 h was observed for all three outcomes, confirming the relevance of this observation. Our 19-hour surgical delay is in good agreement with previously published studies showing that an early surgical intervention improves the neurological recovery [5,[13][14][15]. For instance, Umerani et al (2014) [15] reported a mean surgical delay of 18 h, which was associated to a greater proportion of patients improving by at least 2 AIS grades as compared with patients operated on average 53 h post SCI.…”
Section: Discussionsupporting
confidence: 90%
“…A cutoff value approximating 19 h was observed for all three outcomes, confirming the relevance of this observation. Our 19-hour surgical delay is in good agreement with previously published studies showing that an early surgical intervention improves the neurological recovery [5,[13][14][15]. For instance, Umerani et al (2014) [15] reported a mean surgical delay of 18 h, which was associated to a greater proportion of patients improving by at least 2 AIS grades as compared with patients operated on average 53 h post SCI.…”
Section: Discussionsupporting
confidence: 90%
“…In the past several years, however, the controversy regarding the timing of surgical treatment of CCS has essentially been settled. There is now definitive evidence that early surgery, defined as less than 24 hours, is superior to late decompression [16][17][18][19]24,25]. Earlier studies that had failed to demonstrate a difference were usually flawed by defining ''early'' as being 48 hours, 72 hours, or longer [21,22].…”
Section: When Should We Operate?mentioning
confidence: 94%
“…Most studies defined 24 hours as the time limit for "early" surgery, whereas the outcome was usually assessed using the American Spinal Injury Association Impairment Scale. [24][25][26] One patient had cervical spine decompression the day after his admission due to central cord syndrome. Three patients were put on cervical collar, whereas 1 patient had thoracic extension on top of a cervical collar.…”
Section: Surgical Managementmentioning
confidence: 99%